Figurative language domination in a short story about an impoverished girl - Fitri Nur Rizkyani; Danang Dwi Harmoko (LADU: Journal of Languages and Education, 2021)
Background: The dominant figurative language found in The Little Match Girl short story is pleonasm, metaphor and simile. This study is significance to know the message or meaning that the author wants to convey in his/her work. Purpose: This study aims to identify the kinds of figurative language and finding the dominant of the figurative language that are found in The Little Match Girl short story. Design and methods: This research used descriptive qualitative method. Data in the short story of The Little Match Girl is analyzed using the theory of figurative language. Results: The results of this study show that there 8 kinds of figurative language; 4 data from pleonasm, metaphor and simile, 3 data from symbol, 2 data from personification and hyperbole, and 1 data from paradox and repetition.